Diabetes injectable therapy: type 2 diabetes management in Danish practice. (2nd December 2017) - Sterzi, Daniel; Auziere, Sébastien; Jensen, Marie Markert; Lopes, Sandra
Abstract: Most diabetes care is done by GPs in Denmark. This study aimed to identify the barriers for GPs in initiating injectable therapies and reasons for referral to specialists. The web interview conducted included 85 GPs and 30 specialists experienced in type 2 diabetes (T2D). GPs felt more comfortable with initiating the first injectable therapy (defined as a glucagon-like peptide-1 receptor agonist (GLP-1 RA) or basal insulin) than the second (defined as adding a basal insulin in patients treated with a GLP-1 RA (± oral anti-diabetic treatments [OADs]), or adding either a GLP-1 RA or a bolus insulin in patients treated with basal insulin (± OADs). The main barriers to initiating injectables were related to the complexity of available injectable therapies and the lack of comfort with complex patient profiles, namely patients with difficult glycemia control or significant comorbidities, whom GPs would rather refer to specialists. Main attributes that would increase the GPs' comfort level with initiation of injectables are low risk of hypoglycemia, glycemic control improvement and ease of use of the treatment. An injectable therapy with such attributes could help to overcome barriers to initiating injectable in primary care.